ANALISIS PENAWARAN PASAR DAN KUALITAS WEBSITE BEAUTYHAULINDO DALAM MENINGKATKAN PEMBELIAN ULANG DENGAN INTERVENING KEPUASAN PELANGGAN DAN KEPERCAYAAN PELANGGAN - Benny, B; Rachbini, Didik J; Rekarti, Endi (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research aims to examine and analyze factor which affect customer satisfaction, trust, and interest to buy back on beautyhaulindo website that became the object of research which is in the sub category of fashion in online retail cosmetics in Indonesia. The study design used is descriptive and explanatory research type of survey methods. The population is all customer who has bought in year 2017. Estimation maximum likelihood is use from this observation like 100-200 sample and5 observation from each parameter and in this observation have 50 indicators , if estimated is 250 sample. Data were collected using questionnaires given from 250 respondents. The method of analysis used is SEM (Structural Equation Model).The result of the research shows that the market offering variable to the satisfaction of the beautyhaulindo website influence positively and significantly, the variable of website quality to the satisfaction of the beautyhaulindo website influence positively and significantly, the market offering variable toward the trust of beautyhaulindo website influence positively and significantly, customer trust beautyhaulindo website have a positive and significant effect, customer satisfaction variable to the interest of repeat purchase at beautyhaulindo website have positive and significant influence, customer trust variable to repurchase interest in beautyhaulindo website have positive and significant influence. The suggestion for the next observation is use the sub product and add the new variables like brand image and product quality